ANALISIS TEMA DAN NILAI-NILAI DIDAKTIS PADA NOVEL KAMI BUKAN SARJANA KERTAS KARYA J.S KHAIREN - Cinthia Claudia Duma Napitupulu; Junifer Siregar; Vita Riahni Saragih (JOURNAL SAINS STUDENT RESEARCH, 2024)
This thesis aims 1) to describe the themes contained in the novel We're Not Bachelor Papers by J.S Khairen 2) to describe the didactic values ​​contained in the novel We're Not Bachelor Papers by J.S Khairen. This research uses a qualitative descriptive method. Data sources are the novel We're Not Bachelor Ketas by J.S Khairen and books, references, journals and theses. Data collection techniques are reading, listening and note-taking techniques. The data analysis technique uses descriptive analysis techniques. The results of this research show that 1) themes were found that appeared in the novel Kami Bukan Suhu Kertas by J.S Khairen, namely major themes and minor themes. 2) didactic values ​​were found including moral values, social values ​​and religious values ​​that appeared in the novel Kami Bukan Bachelor Paper by J.S Khairen. Thus it can be seen that 1) the theme in the novel "We Are Not Paper Scholars" by JS. Khairen is the main theme, namely the "social theme" outside of personal problems, namely educational problems which describe where students overcome obstacles in the world of college, and additional themes. 2) Results of analysis of the novel "We Are Not Paper Scholars" by JS. This research data obtained from Khairen found three didactic values ​​consisting of: 1. Moral didactic values ​​consisting of three parts (a) hard work, (b). independent, (c). mean it. 2. Social didactic values ​​consist of four parts (a) togetherness, (b) friendship, (c) caring, (d) helping. 3. Religious values ​​which consist of three parts (a) sincerity, (b) prayer, (c) gratitude.